Would You Kill the Fat Man? : The Trolley Problem and What Your Answer Tells Us about Right and Wrong - Edmonds, David, 1964- (Book collections on Project MUSE., 2014)
In this book, David Edmonds, coauthor of the best-selling Wittgenstein's Poker, tells the riveting story of why and how philosophers have struggled with the ethical dilemma posed by the trolley problem. In the process, he provides an entertaining and informative tour through the history of moral philosophy.